Socio-technical system analysis of tribal and settler farmers in the western ghat regions of wayanad district in Kerala - Geetha G Nath (Department of Agricultural Extension, College of Agriculture, 2007)
Agriculture cannot be sustainable unless it is integrated into the existing social systems. Furthermore, it must enhance social justice. Social integration means that the farmers must accept the technology. Optimum adoption of agricultural production innovations is achieved only when a farmer is persuaded to accept a technical innovation, which for him is technically sound, economically feasible, physically possible and politically and socially compatible.